Dental Injuries in Sports: Analysis, Prevention, and Protection - Wojda, Martyna; Wielgosz, Aleksandra (Quality in Sport, 2024)
Introduction and purpose: Participating in sports plays a vital role in maintaining both physical and mental health. However, as the popularity of physical activity increases, so does the incidence of dental injuries. The aim of this scientific paper is to evaluate the effectiveness of various types of mouthguards in preventing sports-related dental injuries and to demonstrate their positive impact on athletes’ overall health. State of knowledge: Dental injuries are prevalent in sports, comprising 31% of all maxillofacial injuries. The most common types of injuries are crown fractures, dislocations, and soft tissue damage. Preventive measures, particularly the use of mouthguards, are the most effective means of reducing these injuries, lowering their incidence by 82-93%. Custom-made mouthguards provide the best protection and comfort, and their use can improve physical endurance. Summary: Mouthguards are an essential component of injury prevention in sports, providing effective protection for the oral cavity and significantly reducing the risk of serious injuries. The use of mouthguards, particularly custom-made, should be a standard practice in contact sports. In addition to protecting the teeth, mouthguards offer additional benefits, such as improving physical endurance and releasing protective substances like chlorhexidine and fluoride, which contribute to oral health. Increasing awareness and enacting legal regulations mandating the use of mouthguards can significantly improve the oral health of athletes.